Kompetensi Manajerial Kepala Sekolah dalam Meningkatkan Mutu Tenaga Pendidik di SMP Negeri 6 Sarolangun - Nurhikmah Nurhikmah (Management of Islamic Education Department, Faculty of Education and Teacher Training, State Islamic University Sulthan Thaha Saifuddin Jambi, 2024)
This study aims to describe the role of school principals’ managerial competence in improving the quality of teachers at SMP Negeri 6 Sarolangun. A qualitative descriptive approach was employed, with data collected through observation, interviews, and documentation. Data analysis was conducted through reduction, presentation, and conclusion drawing. The findings reveal that the principal has effectively implemented managerial competence, as reflected in the improvement of teachers’ knowledge, skills, and attitudes. The principal plays a crucial role in planning, organizing, implementing, and evaluating programs to enhance teacher quality. The implementation of managerial competence contributes to the development of professional, adaptive teachers who are oriented toward improving the quality of learning.